Mortar based on solid waste-based material and preparation method thereof
By using solid waste-based materials in the mortar and adding nano C-S-H seeds and alkanolamines, the problem of low compressive strength in the early stage of cement replacement materials was solved, and efficient solid waste resource utilization and the preparation of low-carbon mortar were achieved. Significantly reduces environmental pollution and manufacturing costs.
Patent Information
- Application Number
- CN202411572826.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-06
AI Technical Summary
In the prior art, the early compressive strength of cement substitutes is low, which limits its large-scale application, and the incomplete treatment of solid waste leads to environmental pollution.
The mortar based on solid waste-based materials is used, and its composition includes cement, metakaolin, waste clay brick powder, limestone powder, calcium carbide slag, quicklime, standard sand, water, nano C-S-H seeds and alkanolamines, through reasonable mixing ratios NanoC-S-H seeds were prepared by co-precipitation method to promote the hydration and chemical synergistic effect of gelled materials.
It significantly improves the early and later compressive strength of the mortar, reduces the amount of cement and carbon emissions, improves the utilization rate of solid waste, reduces environmental pollution, and reduces the manufacturing cost of mortar.
Smart Images

Figure BDA0005120961640000061 
Figure BDA0005120961640000071 
Figure BDA0005120961640000072
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of building materials, and in particular to a mortar based on solid waste materials and a preparation method thereof. Background Art
[0002] At present, my country produces more than 4 billion tons of solid waste every year. If not handled in time, the large amount of stored solid waste will not only occupy a large amount of space, but also cause serious environmental pollution. The survey found that the oxide composition of some solid wastes (such as bagasse ash, carbide slag and waste clay brick powder) is similar to that of silicate cement, mainly composed of CaO, SiO2, Al2O3 and Fe2O3, and has the potential to become a cement substitute. Using these solid wastes as auxiliary cementitious materials to prepare mortar and concrete products can not only fundamentally reduce the amount of cement used, thereby reducing the carbon emissions of the cement industry, but also improve the utilization rate of solid waste and reduce its adverse effects on the ecological environment.
[0003] Low early activity has always been the main factor limiting the large-scale application of cement substitutes. For mortar, this is mainly reflected in the fact that the early compressive strength of mixed cement mortar is lower than that of pure Portland cement mortar. This problem can be effectively solved by optimizing the mix ratio or selecting suitable chemical admixtures according to the composition of cementitious materials, because mortar is prepared by mixing multiple components, and changes in the characteristics of each component may have a significant impact on its performance. In summary, the use of appropriate cementitious material composition supplemented by effective activity stimulation methods is of great practical significance for the preparation of low-carbon, high-compressive strength mortar. Summary of the invention
[0004] In order to fundamentally reduce the pollution caused by solid waste accumulation to the ecological environment, reduce carbon emissions from the cement industry and lower the manufacturing cost of high-performance mortar, the present invention provides a mortar based on solid waste materials and a preparation method thereof.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] A mortar based on solid waste materials, comprising the following components in parts by weight:
[0007] 315-360 parts of cement;
[0008] 13.5-22.5 parts of metakaolin;
[0009] 45-58.5 parts of waste clay brick powder;
[0010] 13.5-27 parts of limestone powder;
[0011] Calcium carbide slag 9-13.5 parts;
[0012] 9 to 13.5 parts of quicklime;
[0013] 1350 parts of standard sand;
[0014] 225 parts of water;
[0015] 5.4-10.8 parts of nano CSH seed crystals;
[0016] 0.09 to 0.225 parts of alkanolamine.
[0017] Furthermore, the preparation operation of the nano CSH seed crystal is as follows: using NaOH solution to treat bagasse ash to obtain sodium silicate solution, the molar ratio of Na / Si is 2:1, and the solid-liquid ratio is 16%; using HNO3 solution to treat carbide slag to obtain calcium nitrate solution, the molar ratio of Ca / NO3 is 1:2, and the solid-liquid ratio is 22%; at 20-25° C., sodium silicate solution is used as a silicon source, calcium nitrate solution is used as a calcium source, and polycarboxylate water reducer is used as a dispersing stabilizer to synthesize the nano CSH seed crystal by co-precipitation method.
[0018] Furthermore, the Ca(OH)2 content of the carbide slag is greater than 80%, and the particle size is 5 to 20 μm.
[0019] Furthermore, the concentrations of the NaOH solution and the HNO3 solution are both 60%; the SiO2 content of the bagasse ash is greater than 75%, and the specific surface area is 525m 2 / kg; the solid content of the polycarboxylate water-reducing agent is 19.8%, and the water reduction rate is greater than 35%; 103g of sodium silicate solution is used as a silicon source, 110g of calcium nitrate solution is used as a calcium source, and 92g of polycarboxylate water-reducing agent is used as a dispersing stabilizer to prepare nano CSH seeds, and the mass fraction of the polycarboxylate water-reducing agent is 7.8%.
[0020] Further, a peristaltic pump was used to drop the sodium silicate solution and the calcium nitrate solution into the polycarboxylate water reducer. The dropwise addition was completed within 30 minutes. During the addition, the pH of the solution was controlled at 11.7±0.1, the stirring rate was 280-300 rpm, and the aging was performed for more than 3 hours after the dropwise addition was completed.
[0021] Furthermore, the cement is ordinary Portland cement with a specific surface area of 355m 2 / kg, of which the C3S content is 59.38%, the C3A content is 7.28%, and the C4AF content is 11.64%.
[0022] Further, the fineness of the metakaolin is through a 1250 mesh sieve, wherein the Al2O3 content is 43.44%, and the SiO2 content is 54.55%;
[0023] The waste clay brick powder has a fineness of passing through a 200-mesh sieve, wherein the Al2O3 content is 12.89%, the SiO2 content is 60.28%, the CaO content is 14.03%, and the Fe2O3 content is 5.47%;
[0024] The particle size of the limestone powder is less than 100 μm, wherein the calcite content is 85% and the dolomite content is 15%;
[0025] The purity of the quicklime is >95%, and the specific surface area is 396m 2 / kg.
[0026] Furthermore, the average particle size of the nano CSH seed crystals is about 152 nm, and the solid content is 19.26%.
[0027] Furthermore, the alkanolamine is diethanol monoisopropanolamine, and the effective content of the alkanolamine is greater than 85%.
[0028] A method for preparing mortar based on solid waste materials comprises the following steps:
[0029] S1. Weigh the weight of cement, metakaolin, waste clay brick powder, limestone powder, carbide slag and quicklime, and mix them evenly to obtain a cementitious material;
[0030] S2. Weigh various masses of nano-CSH seed crystals, alkanolamine, water and standard sand, and then mix them evenly with the cementitious material to obtain the mortar.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. The nano CSH seed crystals used in the present invention are prepared by co-precipitation after solid waste pretreatment, which not only ensures the purity of the CSH seed crystals, but also realizes the resource utilization of solid waste.
[0033] 2. The metakaolin and waste clay brick powder used in the present invention contain more Al2O3, which can produce chemical synergy with limestone powder, promote the generation of hydration products, and help achieve a higher cement replacement rate. In addition, metakaolin has higher early activity than waste clay brick powder, which can make up for part of the early strength loss caused by the dilution effect. The high alkaline environment is conducive to stimulating the activity of early metakaolin and waste clay brick powder. The alkalinity of the mixed cement slurry is increased by calcium carbide slag and quicklime, which further improves the early hydration degree. The heat release of quicklime dissolution will also increase the hydration reaction rate. The various cementitious materials have different particle size distributions and can fill each other, which is conducive to the formation of a dense microstructure.
[0034] 3. The present invention adds CSH seed crystals and alkanolamines at the same time, which can greatly improve the hydration degree of the gelling system. The role of CSH seed crystals in the gelling system is mainly manifested in promoting the hydration of silicate minerals and the volcanic ash reaction of auxiliary gelling materials. In addition to promoting cement hydration and the volcanic ash reaction of auxiliary gelling materials, alkanolamines can also promote the reaction between the aluminum phase in cement, metakaolin and waste clay brick powder and limestone, and promote the generation of more hydration products.
[0035] 4. The present invention uses a variety of solid wastes as raw materials. On the one hand, it improves the utilization rate of solid wastes and reduces their pollution to the ecological environment. On the other hand, it reduces the amount of cement without affecting the performance of the mortar, thus reducing carbon emissions from the source and reducing the manufacturing cost of the mortar. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0037] In the embodiment of the present invention, the preparation operation of nano CSH seed crystals is as follows: using NaOH solution to treat bagasse ash to obtain sodium silicate solution, the molar ratio of Na / Si is 2:1, and the solid-liquid ratio is 16%; using HNO3 solution to treat carbide slag to obtain calcium nitrate solution, the molar ratio of Ca / NO3 is 1:2, and the solid-liquid ratio is 22%; at 20-25° C., using 103 g of sodium silicate solution as a silicon source, 110 g of calcium nitrate solution as a calcium source, and 92 g of polycarboxylate water reducer as a dispersing stabilizer, the nano CSH seed crystals are synthesized by coprecipitation method; wherein the concentrations of the NaOH solution and the HNO3 solution are both 60%; the SiO2 content of the bagasse ash is greater than 75%, and the specific surface area is 525 m 2 / kg; the solid content of the polycarboxylate water-reducing agent is 19.8%, and the water reduction rate is greater than 35%. In the synthesis experiment, it is configured into a solution with a mass fraction of 7.8%.
[0038] In the embodiment of the present invention, the carbide slag used to prepare the mortar and the carbide slag used to prepare the nano-CSH seed crystals are the same carbide slag, with a Ca(OH)2 content of more than 80% and a particle size of 5 to 20 μm.
[0039] In the embodiment of the present invention, a peristaltic pump is used to drop the sodium silicate solution and the calcium nitrate solution into the polycarboxylate water reducer. The dropwise addition is completed within 30 minutes. During this period, the solution pH is controlled at 11.7±0.1, the stirring rate is 280-300 rpm, and the aging is performed for more than 3 hours after the dropwise addition is completed.
[0040] In the embodiment of the present invention, the cement is ordinary Portland cement with a specific surface area of 355m 2 / kg, of which the C3S content is 59.38%, the C3A content is 7.28%, and the C4AF content is 11.64%.
[0041] In the embodiment of the present invention, the fineness of the metakaolin is through a 1250 mesh sieve, wherein the Al2O3 content is 43.44%, and the SiO2 content is 54.55%; the fineness of the waste clay brick powder is through a 200 mesh sieve, wherein the Al2O3 content is 12.89%, the SiO2 content is 60.28%, the CaO content is 14.03%, and the Fe2O3 content is 5.47%; the particle size of the limestone powder is below 100 μm, wherein the calcite content is 85%, and the dolomite content is 15%; the purity of the quicklime is greater than 95%, and the specific surface area is 396 m 2 / kg.
[0042] In the embodiment of the present invention, the average particle size of the nano-CSH seed crystals is about 152 nm, and the solid content is 19.26%.
[0043] In the embodiment of the present invention, the alkanolamine is diethanol monoisopropanolamine, and the effective content of the alkanolamine is greater than 85%.
[0044] Example 1
[0045] As a preferred embodiment of the present invention, this embodiment discloses a mortar based on solid waste materials, and its specific composition is shown in Table 1.
[0046] Table 1
[0047] raw material Weight / portion cement 315 Metakaolin 22.5 Waste clay brick powder 58.5 Limestone powder 27 Carbide slag 13.5 quicklime 13.5 Standard sand 1350 water 225 Nano CSH Seeds 5.4 Diethanol monoisopropanolamine 0.09
[0048] The method for preparing mortar based on solid waste materials in this embodiment comprises the following steps:
[0049] S1. Weigh the cement, metakaolin, waste clay brick powder, limestone powder, carbide slag and quicklime of the respective masses shown in Table 1 and mix them evenly to obtain a cementitious material;
[0050] S2. Weigh the nano-CSH seed crystals, diethanol monoisopropanolamine, water and standard sand of various masses shown in Table 1, and then mix them evenly with the cementitious material to obtain mortar.
[0051] Example 2
[0052] As a preferred embodiment of the present invention, this embodiment discloses a mortar based on solid waste materials, and its specific composition is shown in Table 2.
[0053] Table 2
[0054] raw material Weight / portion cement 360 Metakaolin 13.5 Waste clay brick powder 45 Limestone powder 13.5 Carbide slag 9 quicklime 9 Standard sand 1350 water 225 Nano CSH Seeds 5.4 Diethanol monoisopropanolamine 0.09
[0055] The method for preparing mortar based on solid waste materials in this embodiment comprises the following steps:
[0056] S1. Weigh the cement, metakaolin, waste clay brick powder, limestone powder, carbide slag and quicklime of the respective masses shown in Table 2 and mix them evenly to obtain a cementitious material;
[0057] S2. Weigh the nano-CSH seed crystals, diethanol monoisopropanolamine, water and standard sand of various masses shown in Table 2, and then mix them evenly with the cementitious material to obtain mortar.
[0058] Example 3
[0059] As a preferred embodiment of the present invention, this embodiment discloses a mortar based on solid waste materials, and its specific composition is shown in Table 3.
[0060] Table 3
[0061]
[0062]
[0063] The method for preparing mortar based on solid waste materials in this embodiment comprises the following steps:
[0064] S1. Weigh the cement, metakaolin, waste clay brick powder, limestone powder, carbide slag and quicklime of the respective masses shown in Table 3 and mix them evenly to obtain a cementitious material;
[0065] S2. Weigh the nano-CSH seed crystals, diethanol monoisopropanolamine, water and standard sand of various masses shown in Table 3, and then mix them evenly with the cementitious material to obtain mortar.
[0066] Example 4
[0067] As a preferred embodiment of the present invention, this embodiment discloses a mortar based on solid waste materials, and its specific composition is shown in Table 4.
[0068] Table 4
[0069]
[0070]
[0071] The method for preparing mortar based on solid waste materials in this embodiment comprises the following steps:
[0072] S1. Weigh the cement, metakaolin, waste clay brick powder, limestone powder, carbide slag and quicklime of the respective masses shown in Table 4 and mix them evenly to obtain a cementitious material;
[0073] S2. Weigh the nano-CSH seed crystals, diethanol monoisopropanolamine, water and standard sand of various masses shown in Table 4, and then mix them evenly with the cementitious material to obtain mortar.
[0074] Example 5
[0075] As a preferred embodiment of the present invention, this embodiment discloses a mortar based on solid waste materials, and its specific composition is shown in Table 5.
[0076] Table 5
[0077] raw material Weight / portion cement 315 Metakaolin 22.5 Waste clay brick powder 58.5 Limestone powder 27 Carbide slag 13.5 quicklime 13.5 Standard sand 1350 water 225 Nano CSH Seeds 10.8 Diethanol monoisopropanolamine 0.09
[0078] The method for preparing mortar based on solid waste materials in this embodiment comprises the following steps:
[0079] S1. Weigh the cement, metakaolin, waste clay brick powder, limestone powder, carbide slag and quicklime of the respective masses shown in Table 5 and mix them evenly to obtain a cementitious material;
[0080] S2. Weigh the nano-CSH seed crystals, diethanol monoisopropanolamine, water and standard sand of various masses shown in Table 5, and then mix them evenly with the cementitious material to obtain mortar.
[0081] Example 6
[0082] As a preferred embodiment of the present invention, this embodiment discloses a mortar based on solid waste materials, and its specific composition is shown in Table 6.
[0083] Table 6
[0084] raw material Weight / portion cement 360 Metakaolin 13.5 Waste clay brick powder 45 Limestone powder 13.5 Carbide slag 9 quicklime 9 Standard sand 1350 water 225 Nano CSH Seeds 5.4 Diethanol monoisopropanolamine 0.225
[0085] The method for preparing mortar based on solid waste materials in this embodiment comprises the following steps:
[0086] S1. Weigh the cement, metakaolin, waste clay brick powder, limestone powder, carbide slag and quicklime of the respective masses shown in Table 6 and mix them evenly to obtain a cementitious material;
[0087] S2. Weigh the nano-CSH seed crystals, diethanol monoisopropanolamine, water and standard sand of various masses shown in Table 6, and then mix them evenly with the cementitious material to obtain mortar.
[0088] Example 7
[0089] As a preferred embodiment of the present invention, this embodiment discloses a mortar based on solid waste materials, and its specific composition is shown in Table 7.
[0090] Table 7
[0091] raw material Weight / portion cement 360 Metakaolin 13.5 Waste clay brick powder 45 Limestone powder 13.5 Carbide slag 9 quicklime 9 Standard sand 1350 water 225 Nano CSH Seeds 10.8 Diethanol monoisopropanolamine 0.09
[0092] The method for preparing mortar based on solid waste materials in this embodiment comprises the following steps:
[0093] S1. Weigh the cement, metakaolin, waste clay brick powder, limestone powder, carbide slag and quicklime of the respective masses shown in Table 7 and mix them evenly to obtain a cementitious material;
[0094] S2. Weigh the nano-CSH seed crystals, diethanol monoisopropanolamine, water and standard sand of various masses shown in Table 7, and then mix them evenly with the cementitious material to obtain mortar.
[0095] Example 8
[0096] As a preferred embodiment of the present invention, this embodiment discloses a mortar based on solid waste materials, and its specific composition is shown in Table 8.
[0097] Table 8
[0098]
[0099]
[0100] The method for preparing mortar based on solid waste materials in this embodiment comprises the following steps:
[0101] S1. Weigh the cement, metakaolin, waste clay brick powder, limestone powder, carbide slag and quicklime of the respective masses shown in Table 8 and mix them evenly to obtain a cementitious material;
[0102] S2. Weigh the nano-CSH seed crystals, diethanol monoisopropanolamine, water and standard sand of various masses shown in Table 8, and then mix them evenly with the cementitious material to obtain mortar.
[0103] Example 9
[0104] As a preferred embodiment of the present invention, this embodiment discloses a mortar based on solid waste materials, and its specific composition is shown in Table 9.
[0105] Table 9
[0106]
[0107]
[0108] The method for preparing mortar based on solid waste materials in this embodiment comprises the following steps:
[0109] S1. Weigh the cement, metakaolin, waste clay brick powder, limestone powder, carbide slag and quicklime of the respective masses shown in Table 9 and mix them evenly to obtain a cementitious material;
[0110] S2. Weigh the nano-CSH seed crystals, diethanol monoisopropanolamine, water and standard sand of various masses shown in Table 9, and then mix them evenly with the cementitious material to obtain mortar.
[0111] Comparative Example 1
[0112] The present comparative example is compared with Example 6, except that nano-CSH seed crystals and diethanol monoisopropanolamine are not added in the present comparative example, and other conditions are the same to obtain a comparative mortar.
[0113] Comparative Example 2
[0114] The difference between this comparative example and Example 6 is that the cementitious material in this comparative example is only ordinary Portland cement and no nano CSH seeds and diethanol monoisopropanolamine are added, and the other conditions are the same to obtain a comparative mortar.
[0115] Comparative Example 3
[0116] Compared with Example 6, the difference between this comparative example is that the cementitious material in this comparative example is only ordinary Portland cement, and the other conditions are the same, thereby obtaining a comparative mortar.
[0117] Comparative Example 4
[0118] Compared with Example 6, the difference between this comparative example is that in this comparative example, diethanol monoisopropanolamine is replaced by monoethanol diisopropanolamine, and other conditions are the same to obtain a comparative mortar.
[0119] Test Case
[0120] With reference to the national standard “GB / T 1346-2011 Test method for water consumption, setting time and stability of cement standard consistency”, the setting time of Examples 1 to 9 and Comparative Examples 1 to 4 was tested, and the test results are shown in Table 10; with reference to the national standard “GB / T 17671-2021 Test method for strength of cement mortar (ISO method)”, the compressive strength of each mortar at different ages was tested, and the test results are shown in Table 11.
[0121] Table 10
[0122]
[0123]
[0124] As shown in the data in Table 10, the initial setting time of the embodiment and the comparative example is 75-154min, and the final setting time is 125-284min, which meets the requirements of the national standard GB175-2023 for cement setting time. Whether it is in the silicate cement system, that is, the cementitious material is only ordinary silicate cement, or in the mixed cement system adding solid waste, diethanol monoisopropanolamine / monoethanol diisopropanolamine and nano CSH seeds all significantly shorten the initial setting and final setting time. By comparing Example 3, Example 8 and Example 9, Comparative Example 1, Example 4 and Example 5, Comparative Example 2, Example 6 and Example 7, it can be found that the amount of admixture (nano CSH seeds / diethanol monoisopropanolamine) is higher, and the accelerating effect is more significant. In addition, the accelerating effect of monoethanol diisopropanolamine is slightly weaker than diethanol monoisopropanolamine.
[0125] Table 11
[0126]
[0127]
[0128] As shown in the data in Table 11, in the early stage (1d and 3d), the compressive strength of some mixed cement mortars (such as Example 7 and Example 9) is higher than that of pure cement mortar (Comparative Example 2), which is mainly due to the promotion of diethanol monoisopropanolamine and nano CSH seeds to the hydration of cementitious materials. At the age of 28d, the compressive strength of all embodiments is much higher than that of pure cement mortar. By comparing Example 3, Example 8 and Example 9, Comparative Example 1, Example 4 and Example 5, Comparative Example 2, Example 6 and Example 7, it can be found that the higher the amount of admixture (nano CSH seeds / diethanol monoisopropanolamine), the more significant the enhancement effect. In addition, the results of Example 6 and Comparative Example 4 show that the 1d enhancement effect of monoethanol diisopropanolamine is significantly weaker than diethanol monoisopropanolamine, and the 3d enhancement effect is comparable, and the 28d enhancement effect is slightly stronger than diethanol monoisopropanolamine.
[0129] The present invention prepares a mortar based on solid waste materials by using a suitable cementitious material composition and an effective activity stimulation method. The setting time of the mortar meets the requirements of national standards and has high early and late strengths. In addition, a variety of bulk solid wastes are used in the preparation process of the mortar, which is helpful for the implementation of energy conservation and emission reduction strategies in the cement industry.
[0130] Finally, it should be noted that the above embodiments are only preferred embodiments of the present invention to illustrate the technical solutions of the present invention, rather than limiting them, and certainly not limiting the patent scope of the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. In other words, any changes or modifications made to the main design concept and spirit of the present invention that have no substantive significance, and the technical problems they solve are still consistent with the present invention, should be included in the protection scope of the present invention. In addition, the direct or indirect application of the technical solutions of the present invention in other related technical fields is also included in the patent protection scope of the present invention.
Claims
1. A mortar based on solid waste materials, characterized in that: The composition comprises the following components in parts by weight: 315-360 parts of cement; 13.5-22.5 parts of metakaolin; 45-58.5 parts of waste clay brick powder; 13.5-27 parts of limestone powder; Calcium carbide slag 9-13.5 parts; 9 to 13.5 parts of quicklime; 1350 parts of standard sand; 225 parts of water; 5.4-10.8 parts of nano CSH seed crystals; 0.09 to 0.225 parts of alkanolamine.
2. The mortar based on solid waste materials according to claim 1, characterized in that: The preparation operation of the nano CSH seed crystal is as follows: using NaOH solution to treat bagasse ash to obtain sodium silicate solution, the molar ratio of Na / Si is 2:1, and the solid-liquid ratio is 16%; using HNO3 solution to treat carbide slag to obtain calcium nitrate solution, the molar ratio of Ca / NO3 is 1:2, and the solid-liquid ratio is 22%; at 20-25° C., using sodium silicate solution as a silicon source, calcium nitrate solution as a calcium source, and polycarboxylate water reducer as a dispersing stabilizer, the nano CSH seed crystal is synthesized by coprecipitation method.
3. A mortar based on solid waste materials according to claim 1 or 2, characterized in that: The Ca(OH)2 content of the carbide slag is greater than 80%, and the particle size is 5 to 20 μm.
4. The mortar based on solid waste materials according to claim 2, characterized in that: The concentrations of the NaOH solution and the HNO3 solution are both 60%; the SiO2 content of the bagasse ash is greater than 75%, and the specific surface area is 525m 2 / kg; the solid content of the polycarboxylate water-reducing agent is 19.8%, and the water reduction rate is greater than 35%; 103g of sodium silicate solution is used as a silicon source, 110g of calcium nitrate solution is used as a calcium source, and 92g of polycarboxylate water-reducing agent is used as a dispersing stabilizer to prepare nano CSH seeds, and the mass fraction of the polycarboxylate water-reducing agent is 7.8%.
5. The mortar based on solid waste materials according to claim 2, characterized in that: The sodium silicate solution and the calcium nitrate solution were added dropwise to the polycarboxylate water reducer using a peristaltic pump. The addition was completed within 30 minutes. During this period, the pH of the solution was controlled at 11.7±0.1, the stirring rate was 280-300 rpm, and the aging was performed for more than 3 hours after the addition was completed.
6. The mortar based on solid waste materials according to claim 1, characterized in that: The cement is ordinary Portland cement with a specific surface area of 355m 2 / kg, of which the C3S content is 59.38%, the C3A content is 7.28%, and the C4AF content is 11.64%.
7. The mortar based on solid waste materials according to claim 1, characterized in that: The metakaolin has a fineness of passing through a 1250 mesh sieve, wherein the Al2O3 content is 43.44% and the SiO2 content is 54.55%; The waste clay brick powder has a fineness of passing through a 200-mesh sieve, wherein the Al2O3 content is 12.89%, the SiO2 content is 60.28%, the CaO content is 14.03%, and the Fe2O3 content is 5.47%; The particle size of the limestone powder is less than 100 μm, wherein the calcite content is 85% and the dolomite content is 15%; The purity of the quicklime is >95%, and the specific surface area is 396m 2 / kg.
8. The mortar based on solid waste materials according to claim 1, characterized in that: The average particle size of the nano CSH seed crystals is about 152 nm, and the solid content is 19.26%.
9. The mortar based on solid waste materials according to claim 1, characterized in that: The alkanolamine is diethanol monoisopropanolamine, and the effective content of the alkanolamine is greater than 85%.
10. A method for preparing mortar based on solid waste materials according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Weigh the weight of cement, metakaolin, waste clay brick powder, limestone powder, carbide slag and quicklime, and mix them evenly to obtain a cementitious material; S2. Weigh various masses of nano-CSH seed crystals, alkanolamine, water and standard sand, and then mix them evenly with the cementitious material to obtain the mortar.
Citation Information
Patent Citations
Waste glass-carbide slag-based C-S-H gel nanocrystal nucleus early strength agent as well as preparation method and application thereof
CN115231846A
Recycled polymer concrete material and preparation method thereof
CN116589240A
Multi-element solid waste-based recycled concrete and preparation method thereof
CN118344093A
High-temperature-resistant geopolymer mortar based on regenerated clay brick powder and preparation method of high-temperature-resistant geopolymer mortar
CN118545941A